THE GREAT POWER SPACE RACE: HOW THE US, RUSSIA AND CHINA COMPETING IN SPACE EXPLORATION - Nauman Ali; Tariq Amin; Professor Dr. Asia Kareem Awaan (International Journal of Contemporary Issues in Social Sciences, 2024)
The modern space race among the Joined together States, Russia, and China is a complex marvel driven by a huge number of components, counting geopolitical control, financial interface, logical disclosure, national glory, asset utilization, colonization, inspiration, inventive headway, financial improvement, national security, worldwide participation, and long-term survival. This competition has driven to critical accomplishments in space investigation, counting lunar missions, space stations, carry programs, and heavy-lift rockets.The Joined together States, Russia, and China have accomplished momentous points of reference in space investigation, illustrating their mechanical capabilities and progressing human information. The Artemis program, lunar investigate stations, and heavy-lift rockets are confirmations to their inventive ability. Worldwide participation, such as the Universal Space Station program, has moreover encouraged collaboration and information sharing among nations.However, the space race has moreover been stamped by mischances and disappointments, coming about in the misfortune of lives and shuttle. These mishaps serve as a piercing update of the dangers and challenges inalienable in space investigation. In spite of these challenges, space organizations and private companies proceed to thrust the boundaries of space investigation, driven by the interest of logical disclosure, financial benefits, and national prestige.The benefits of space investigation expand past national interface, contributing to human headway and understanding of the universe. Space inquire about has driven to various spin-off advances, moving forward day by day life, commerce, and rousing future eras to seek after careers in science, innovation, building, and arithmetic (STEM).